A Systematic Review of the Rates of Depression in Children and Adults With High-Functioning Autism Spectrum Disorder. Issue 4 (2nd October 2017) - Wigham, Sarah; Barton, Stephen; Parr, Jeremy R.; Rodgers, Jacqui
ABSTRACT: Accurate population rates of depression can inform allocation of health resources and service planning, to counter the impact of depression on quality of life and morbidity. A systematic review of the rates of depression in children and adults with autism spectrum disorders (ASD) and without intellectual disability (high-functioning [HF] ASD) was conducted. Nineteen studies met inclusion criteria. Reported rates of depression varied; the reasons for this are discussed including availability of psychometrically valid and reliable measures of depression for people with HF ASD, and heterogeneity of study design. Further examination of the phenomenology of depression in HF ASD linked to the development of psychometrically valid assessment measures would facilitate epidemiological studies, improve clinical case recognition, and inform treatments and interventions.